Don’t Always Prefer My Chosen Objects: Low Level of Trait Autonomy and Autonomy Deprivation Decreases Mere Choice Effect - Shang, Zhe; Tao, Tuoxin; Wang, Lei (Frontiers in Psychology, 2016)
Choice effect is a robust phenomenon in which even “mere choice” that does not include actual choosing actions could result in more preference for the self-chosen objects over other-chosen objects. In the current research, we proposed that autonomy would impact the mere choice effect. We conducted two studies to examine the hypothesis. The results showed that the mere choice effect measured by Implicit Association Test (IAT) significantly decreased for participants with lower levels of trait autonomy (Study 1) and when participants were primed to experience autonomy deprivation (Study 2). The theoretical and practical implications are discussed.